A method for producing a nickel-titanium particle-reinforced magnesium-based composite material and the product

CN122895503APending Publication Date: 2026-10-13CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044323.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但现有的NiTi增强金属基复合材料研究表面,仅将NiTi颗粒与镁合金进行简单复合,是不能充分开发和利用NiTi颗粒的微观相变潜能,致使材料性能提高有限,这也是当前该领域亟待克服的技术空白

Benefits of technology

[0014]本发明的有益效果在于:本发明提供了一种镍钛颗粒增强镁基复合材料的制备方法及产品,由本发明中的方法制备的镁基复合材料表现出了优异的力学性能,室温下屈服强度可达440 MPa左右,极限抗拉强度可达460 MPa左右,延伸率维持在8.0%左右。且该镁基复合材料制备方法简单,且原料易得,适合大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895503A_ABST
    Figure CN122895503A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a nickel-titanium particle reinforced magnesium-based composite material and a product, and the preparation method is as follows: NiTi alloy powder and magnesium alloy powder are uniformly mixed through ball milling, vacuum hot-pressing sintering is carried out, and then solid solution treatment and hot deformation treatment are carried out, so that the magnesium-based composite material can be obtained. The magnesium-based composite material exhibits excellent mechanical properties, the yield strength at room temperature can reach about 440 MPa, the ultimate tensile strength can reach about 460 MPa, and the elongation rate is maintained at about 8.0%. The preparation method of the magnesium-based composite material is simple, raw materials are easy to obtain, and the method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnesium alloy materials technology, specifically to a method for preparing a nickel-titanium particle-reinforced magnesium-based composite material and the product thereof. Background Technology

[0002] Magnesium alloys, as the lightest engineering metal structural materials currently available, have great application potential in lightweight fields such as aerospace, rail transportation, and 3C electronics. However, the relatively low absolute strength of magnesium alloys severely limits their widespread use in high-end load-bearing structural components.

[0003] To improve the mechanical properties of magnesium alloys, introducing heterogeneous reinforcing particles into the magnesium matrix to prepare metal matrix composites is one of the most effective methods currently available. However, existing particle reinforcement techniques have significant limitations. On the one hand, traditional non-metallic ceramic particles have poor physical wettability with the magnesium matrix, easily leading to severe stress concentration at the interface during deformation under stress, resulting in interface debonding and premature brittle fracture of the material. The plasticity of ceramic particle-reinforced metal matrix composites severely limits their application. On the other hand, although traditional pure metallic rigid particles improve interfacial bonding, they mostly exist as absolutely rigid inclusions during hot working and tensile deformation, making it difficult to achieve effective synergistic deformation with the soft magnesium matrix. This huge abrupt change in elastic modulus causes the strengthening efficiency of composite materials to easily encounter bottlenecks, making it difficult to achieve a leapfrog breakthrough in strength and plasticity.

[0004] NiTi shape memory alloys not only possess excellent mechanical strength but also unique stress-induced martensitic phase transformation characteristics and high strain compatibility, theoretically making them an ideal reinforcement for metal matrix composites. However, existing research on NiTi-reinforced metal matrix composites shows that simply combining NiTi particles with magnesium alloys cannot fully develop and utilize the microscopic phase transformation potential of NiTi particles, resulting in limited improvement in material properties. This is a technological gap that urgently needs to be overcome in this field. Summary of the Invention

[0005] In view of this, one objective of the present invention is to provide a method for preparing a nickel-titanium particle-reinforced magnesium matrix composite material; the other objective is to provide a nickel-titanium particle-reinforced magnesium matrix composite material.

[0006] To achieve the above objectives, the present invention provides the following technical solution: 1. A method for preparing a nickel-titanium particle reinforced magnesium matrix composite material, the method being as follows: NiTi alloy powder and magnesium alloy powder are ball-milled and mixed, then vacuum hot-pressed and sintered, followed by solution treatment and hot deformation treatment; the amount of NiTi alloy powder added is 6-10 wt.% of the total mass of NiTi alloy powder and magnesium alloy powder.

[0007] Preferably, the ball milling and mixing specifically involves: under a protective atmosphere, ball milling at a ball-to-material ratio of 3-6:1 and a rotation speed of 50-100 rpm for 2-4 hours.

[0008] Preferably, the vacuum hot pressing sintering is specifically performed as follows: heating to 480-520℃ under a pressure of 5-10 kN, then holding at that temperature and increasing the pressure to 80-120 kN, holding at that temperature and pressure for 20-50 minutes, and then cooling with the furnace.

[0009] Preferably, the solution treatment specifically involves performing a solution treatment at 500-550°C for 8-14 hours.

[0010] Preferably, the hot deformation treatment specifically involves: preheating the extrusion die and the billet to 320-400℃ and holding them at that temperature for 1-3 hours, followed by hot extrusion at an extrusion ratio of 10-20:1 and an extrusion speed of 0.05-0.2 mm / s.

[0011] Preferably, the NiTi alloy powder is spherical Ni with a particle size ranging from 1 to 30 μm. 55 Ti 45 powder.

[0012] Preferably, the magnesium alloy powder is spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70μm.

[0013] 2. The nickel-titanium particle-reinforced magnesium matrix composite material prepared by the preparation method described above.

[0014] The beneficial effects of this invention are as follows: This invention provides a method for preparing a nickel-titanium particle-reinforced magnesium matrix composite material and a product thereof. The magnesium matrix composite material prepared by the method of this invention exhibits excellent mechanical properties, with a yield strength of approximately 440 MPa at room temperature, an ultimate tensile strength of approximately 460 MPa, and an elongation maintained at approximately 8.0%. Furthermore, the preparation method of this magnesium matrix composite material is simple, and the raw materials are readily available, making it suitable for large-scale production.

[0015] This invention, by controlling the amount of NiTi alloy powder added, utilizes extrusion shear stress to induce the formation of a severely deformed outer shell containing B19' martensite and high-density surface defects in NiTi particles, while retaining the B2 phase and transitional R phase reinforcing core. This severely deformed outer shell forms a buffer layer between the reinforcing core and the soft magnesium matrix, constructing a strain gradient region with a smooth transition in elastic modulus. On the one hand, under macroscopic tensile stress, this strain gradient region effectively coordinates the strain distribution between the two phases through the slippage and deformation of internal surface defects, achieving synergistic deformation. This fundamentally overcomes the technical bottleneck of traditional non-metallic ceramic particles or pure rigid metal particles easily inducing stress concentration, interface debonding, and microcrack initiation. On the other hand, the uncoordinated deformation between multi-level interfaces not only induces extremely high density of geometrically necessary dislocations, triggering a strong heterogeneous deformation-induced strengthening effect; simultaneously, the highly concentrated local distortion energy at the NiTi particle interface significantly reduces the recrystallization nucleation barrier, stimulating a strong particle-induced nucleation effect, promoting the formation of a large number of fine dynamic recrystallized grains around the particles. The three mechanisms work synergistically to significantly improve the overall mechanical properties of composite materials.

[0016] Furthermore, the outward diffusion of Ni atoms within the particles induces an in-situ reaction, generating a thermodynamically stable LPS0 phase. This in-situ consumption process effectively prevents the formation of traditional brittle interface phases (such as Mg2Ni), reducing the risk of interface embrittlement and improving the strong and tough bonding of the interface. Under hot extrusion stress, the originally randomly oriented elongated LPSO phases are re-aligned along the extrusion direction, constructing an oriented framework. Leveraging its highly coherent interface, this framework acts as a short fiber reinforcement, effectively bearing the main load transferred from the softer magnesium matrix, thereby significantly enhancing the macroscopic strength of the composite material. Simultaneously, a certain degree of particle-induced nucleation effect occurs around the LPSO phase, aiding in the refinement of local grains and further perfecting the multi-scale synergistic strengthening system of the material. Attached Figure Description

[0017] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the following figures are provided for illustration: Figure 1 This is a 200x SEM image of the nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1. Figure 2 The image shows a 1500x SEM image of the nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1, along with the corresponding EDS point-source elemental analysis results. Figure 3 The figure shows the NiTi / Mg interface analysis results in the nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1. Figure 3 Image (a) is a transmission electron microscope image. Figure 3(b) shows the nanoscale transmission Kikuchi diffraction pattern. Figure 3 (c) shows the local orientation difference distribution. Figure 4 The figures show the NiTi / Mg interface analysis results in the nickel-titanium particle-reinforced magnesium matrix composites prepared in Comparative Example 2 (3NiTi / VW63-E), Example 2 (6NiTi / VW63-E), Example 1 (10NiTi / VW63-E), and Comparative Example 3 (20NiTi / VW63-E). Figure 4 In the middle (a), the transmission electron microscope image of Comparative Example 2 (3NiTi / VW63-E) is shown. Figure 4 Image (b) is a transmission electron microscope (TEM) image of Example 2 (6NiTi / VW63-E). Figure 4 Image (c) is a transmission electron microscope (TEM) image of Example 1 (10NiTi / VW63-E). Figure 4 The middle (d) image is a transmission electron microscope image of Comparative Example 3 (20NiTi / VW63-E). Detailed Implementation

[0018] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0019] Example 1

[0020] Preparation of nickel-titanium particle-reinforced magnesium matrix composite material (10NiTi / VW63-E) S1: Proportioning by mass: Take spherical Ni particles with a particle size range of 1-30μm. 55 Ti 45 Spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70 μm. Among them, spherical Ni... 55 Ti 45 The amount of powder added is spherical Ni 55 Ti 45 10 wt.% of the total mass of powder and spherical Mg-6Gd-3Y-0.5Zr alloy powder. S2: Ball milling and mixing: Pour the two powders from step S1 into a ball mill jar, and under the protection of argon atmosphere, ball mill at a speed of 80 rpm for 3 hours at a ball-to-powder ratio of 4:1 to obtain mixed powder. S3: Vacuum hot pressing sintering: The mixed powder obtained in step S2 is placed in a vacuum hot pressing sintering furnace, heated to 500°C under a pressure of 8kN, then held at the temperature and pressure increased to 100kN, held at the temperature and pressure for 30 minutes, and cooled with the furnace to obtain the sintered billet; S4: Solution treatment: The sintered billet obtained in step S3 is solution treated at 540°C for 12 hours; S5: Hot deformation treatment: After preheating the billet and extrusion die treated in step S4 to 360°C and holding for 2 hours, hot extrusion is carried out at an extrusion ratio of 16:1 and an extrusion speed of 0.1 mm / s.

[0021] The nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1 was characterized by scanning electron microscopy at 200x magnification, and the results are as follows: Figure 1 As shown, by Figure 1 It can be seen that NiTi particles exhibit excellent dispersion and uniform distribution in the magnesium matrix, and form a streamlined arrangement along the extrusion direction. The generated LPSO phase is elongated and uniformly distributed along the extrusion direction, forming a directional framework.

[0022] The nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1 was characterized by scanning electron microscopy and energy dispersive spectroscopy at 1500x magnification. The results are as follows: Figure 2 As shown, by Figure 2 It can be seen that the magnesium matrix and NiTi particles are well bonded, and no obvious interface products or defects are observed. The elongated phase is uniformly interspersed between the matrix and particles, and is arranged in the direction of compression. EDS point-source elemental analysis at points A, B, C, and D on the elongated phase reveals that it is mainly composed of Mg, Ni, Gd, and Y elements, confirming that this phase is an LPSO phase.

[0023] The NiTi / Mg interface of the nickel-titanium particle-reinforced magnesium matrix composite material prepared in Example 1 was analyzed after focused ion beam sample preparation. The results are as follows: Figure 3 As shown. Among them, Figure 3 Image (a) is a transmission electron microscope image. Figure 3 (b) shows the nanoscale transmission Kikuchi diffraction pattern. Figure 3 Image (c) shows the local orientation difference distribution. (From...) Figure 3 As shown in (a), under the enormous shear stress of hot extrusion, NiTi particles form a severely deformed outer shell containing B19' martensite and high-density surface defects, while retaining the B2 phase and transitional R phase reinforcing core. The NiTi particles thus construct a unique "core-shell" heterostructure in situ. Combined with... Figure 3 (b) and Figure 3As shown in (c), during the deformation process, not only do high-density geometrically necessary dislocations (GNDs) accumulate in the matrix surrounding the particles, but the core region of the NiTi particles also exhibits extremely high KAM values, while the shell region of the particles shows an unresolved region (highly surface defects or amorphization). This high-density dislocation network spanning the phase interface proves that the core-shell structure and the matrix underwent deep synergistic deformation. The significant plastic deformation incoordination between the multi-level interfaces induced strong back stress, which in turn induced a heterogeneous deformation-induced strengthening effect. This mechanism enables the material to exhibit a high work hardening rate on a macroscopic scale, achieving an increase in yield strength and ultimate tensile strength. On the other hand, the severely deformed outer shell containing B19' martensite and high-density surface defects acts as an effective buffer layer, constructing a strain gradient region with a smooth transition in elastic modulus between the hard NiTi particle core and the soft magnesium matrix. Under tensile stress, the shell can effectively coordinate the strain mismatch between the two phases through the micro-slip of surface defects and reversible deformation, significantly delaying crack initiation, thus ensuring good plasticity of the material even at high strength.

[0024] Example 2

[0025] Preparation of nickel-titanium particle-reinforced magnesium matrix composite material (6NiTi / VW63-E) S1: Proportioning by mass: Take spherical Ni particles with a particle size range of 1-30μm. 55 Ti 45 Spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70 μm. Among them, spherical Ni... 55 Ti 45 The amount of powder added is spherical Ni 55 Ti 45 The total mass of the powder and the spherical Mg-6Gd-3Y-0.5Zr alloy powder was 6 wt.%. S2: Ball milling and mixing: Pour the two powders from step S1 into a ball mill jar, and under the protection of argon atmosphere, ball mill at 100 rpm for 2 hours at a ball-to-powder ratio of 6:1 to obtain mixed powder. S3: Vacuum hot pressing sintering: The mixed powder obtained in step S2 is placed in a vacuum hot pressing sintering furnace, heated to 480°C under a pressure of 10kN, then held at the temperature and pressure to 80kN, held at the temperature and pressure for 50min, and cooled with the furnace to obtain the sintered billet. S4: Solution treatment: The sintered billet obtained in step S3 is solution treated at 500°C for 14 hours; S5: Hot deformation treatment: After preheating the billet and extrusion die treated in step S4 to 320℃ and holding for 3 hours, hot extrusion is carried out at an extrusion ratio of 20:1 and an extrusion speed of 0.2mm / s.

[0026] Comparative Example 1 Preparation of magnesium-based composite material (VW63-E) S1: Prepare materials by mass ratio: Take spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70μm; S2: Ball milling and mixing: Pour the spherical Mg-6Gd-3Y-0.5Zr alloy powder from step S1 into a ball mill jar, and under argon atmosphere protection, ball mill at 50 rpm for 3 hours at a ball-to-powder ratio of 3:1 to obtain mixed powder. S3: Vacuum hot pressing sintering: The mixed powder obtained in step S2 is placed in a vacuum hot pressing sintering furnace, heated to 500°C under a pressure of 8kN, then held at the temperature and pressure to 120kN for 20 minutes, and cooled with the furnace to obtain the sintered billet. S4: Solution treatment: The sintered billet obtained in step S3 is solution treated at 520°C for 10 hours; S5: Hot deformation treatment: After preheating the billet and extrusion die treated in step S4 to 360°C and holding for 1.5 hours, hot extrusion is carried out at an extrusion ratio of 18:1 and an extrusion speed of 0.05 mm / s.

[0027] Comparative Example 2 Preparation of nickel-titanium particle-reinforced magnesium matrix composite material (3NiTi / VW63-E) S1: Proportioning by mass: Take spherical Ni particles with a particle size range of 1-30μm. 55 Ti 45 Spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70 μm. Among them, spherical Ni... 55 Ti 45 The amount of powder added is spherical Ni 55 Ti 45 3 wt.% of the total mass of powder and spherical Mg-6Gd-3Y-0.5Zr alloy powder. S2: Ball milling and mixing: Pour the two powders from step S1 into a ball mill jar, and under the protection of argon atmosphere, ball mill at a speed of 80 rpm for 4 hours at a ball-to-powder ratio of 5:1 to obtain mixed powder. S3: Vacuum hot pressing sintering: The mixed powder obtained in step S2 is placed in a vacuum hot pressing sintering furnace, heated to 520°C under a pressure of 10kN, then held at the temperature and pressure to 100kN for 30 minutes, and then cooled with the furnace to obtain the sintered billet. S4: Solution treatment: The sintered billet obtained in step S3 is solution treated at 500°C for 14 hours; S5: Hot deformation treatment: After preheating the billet and extrusion die treated in step S4 to 320℃ and holding for 3 hours, hot extrusion is carried out at an extrusion ratio of 10:1 and an extrusion speed of 0.15mm / s.

[0028] Comparative Example 3 Preparation of nickel-titanium particle-reinforced magnesium matrix composite material (20NiTi / VW63-E) S1: Proportioning by mass: Take spherical Ni particles with a particle size range of 1-30μm. 55 Ti 45 Spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70 μm. Among them, spherical Ni... 55 Ti 45 The amount of powder added is spherical Ni 55 Ti 45 20 wt.% of the total mass of powder and spherical Mg-6Gd-3Y-0.5Zr alloy powder. S2: Ball milling and mixing: Pour the two powders from step S1 into a ball mill jar, and under the protection of argon atmosphere, ball mill at 100 rpm for 2 hours at a ball-to-powder ratio of 4:1 to obtain mixed powder. S3: Vacuum hot pressing sintering: The mixed powder obtained in step S2 is placed in a vacuum hot pressing sintering furnace, heated to 480°C under a pressure of 5kN, then held at the temperature and pressure to 80kN, held at the temperature and pressure for 50min, and cooled with the furnace to obtain the sintered billet. S4: Solution treatment: The sintered billet obtained in step S3 is solution treated at 550°C for 8 hours; S5: Hot deformation treatment: After preheating the billet and extrusion die treated in step S4 to 400℃ and holding for 1 hour, hot extrusion is carried out at an extrusion ratio of 12:1 and an extrusion speed of 0.1mm / s.

[0029] The nickel-titanium particle-reinforced magnesium matrix composites prepared in Comparative Example 2 (3NiTi / VW63-E), Example 2 (6NiTi / VW63-E), Example 1 (10NiTi / VW63-E), and Comparative Example 3 (20NiTi / VW63-E) were prepared by focused ion beam sampling. The NiTi / Mg interface in each composite was analyzed, and the results are as follows: Figure 4 As shown. Wherein: Figure 4Image (a) is a transmission electron microscope (TEM) image of Comparative Example 2 (3NiTi / VW63-E). Only the NiTi-Mg phase interface is marked with a red dashed line. It can be seen that the internal contrast of the NiTi particles is relatively uniform, with only some dispersed deformation bands. This demonstrates that at lower NiTi particle addition levels, the extrusion stress is buffered by the excessive rheological properties of the soft magnesium matrix, failing to reach the critical stress at the interface to induce a martensitic phase transformation in the particles, thus preventing the formation of a shell.

[0030] Figure 4 Image (b) is a transmission electron microscope image of Example 2 (6NiTi / VW63-E). The yellow dashed line in the image marks the boundary line inside the particle. It can be seen that there are a lot of surface defects on the outside of the particle, while the inside is relatively intact with only a small number of phase transition bands, showing a core-shell structure. This proves that the stress transmitted to the interface at this time just crosses the phase transition threshold, and a certain degree of phase transition and deformation begins to occur on the periphery of the particle.

[0031] Figure 4 Image (c) is a transmission electron microscope (TEM) image of Example 1 (10NiTi / VW63-E). The yellow dashed line shows a very thick, highly deformed band with prominent surface defects (twins, stacking faults, etc.) surrounding it, while the interior remains relatively intact. This demonstrates that at this addition level, stress transfer and matrix coordination reached a balance, constructing a complete and extremely dense core-shell structure.

[0032] Figure 4 The middle (d) image is a transmission electron microscope image of Comparative Example 3 (20NiTi / VW63-E). The image shows that the NiTi particles are disordered and have no obvious boundary partitions. This proves that with a high amount of NiTi particles, the extremely small particle spacing leads to severe superposition of stress fields. The extremely high local stress makes the entire interior of the particles become high-density surface defects without shell boundaries.

[0033] In summary, the formation of the core-shell structure in the composite material exhibits a specific critical dependence on the amount of NiTi particles added. At a low addition of 3 wt.%, hot extrusion deformation is mainly absorbed by the magnesium matrix, and the shear stress at the particle interface does not reach the stress threshold for inducing martensitic phase transformation on the surface of the NiTi particles. There are no obvious deformation zones within the particles, and a core-shell structure is not formed. When the addition increases to 6-10 wt.%, the shortening of the interparticle spacing restricts the free flow of the matrix, increasing the interfacial stress transfer efficiency and reaching the phase transformation critical point. This causes the formation of a severe deformation zone containing B19' martensite and high-density surface defects (twins, stacking faults) on the particle surface, while the interior retains the B2 and R phases, thus constructing a dense core-shell heterostructure. When the addition further increases to 20 wt.%, the severe stress field superposition between adjacent particles leads to excessively high local stress concentration, causing the entire interior of the NiTi particles to reach the stress threshold for phase transformation and defect formation. This results in the entire particle domain transforming into a high-density surface defect state, losing the interfacial boundary characteristics of the core-shell structure.

[0034] The five materials prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to room temperature tensile tests using a mechanical property testing machine. The specific mechanical properties are shown in Table 1.

[0035] Table 1 Mechanical properties of the materials prepared in the examples and comparative examples

[0036] The results show that the overall mechanical properties of Examples 1-2 are superior to those of Comparative Examples 1-3. The composite material prepared by the method of this invention has a yield strength of about 440 MPa at room temperature, an ultimate tensile strength of about 460 MPa, and an elongation of about 8.0%, proving that the composition design and core-shell structure construction of this invention help to improve the overall mechanical properties of the composite material.

[0037] The above-described embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A method for preparing a nickel-titanium particle-reinforced magnesium matrix composite material, characterized in that, The method is as follows: NiTi alloy powder and magnesium alloy powder are ball-milled and mixed, then vacuum hot-pressed and sintered, followed by solution treatment and hot deformation treatment; the amount of NiTi alloy powder added is 6-10 wt.% of the total mass of NiTi alloy powder and magnesium alloy powder.

2. The preparation method according to claim 1, characterized in that, The ball milling and mixing process specifically involves: under a protective atmosphere, ball milling at a speed of 50-100 rpm for 2-4 hours with a ball-to-material ratio of 3-6:

1.

3. The preparation method according to claim 1, characterized in that, The vacuum hot pressing sintering process specifically involves heating to 480-520℃ under a pressure of 5-10 kN, then holding at that temperature and increasing the pressure to 80-120 kN for 20-50 minutes, followed by cooling in the furnace.

4. The preparation method according to claim 1, characterized in that, The solution treatment specifically involves performing a solution treatment at 500-550℃ for 8-14 hours.

5. The preparation method according to claim 1, characterized in that, The hot deformation treatment specifically involves preheating the extrusion die and the billet to 320-400℃ and holding them at that temperature for 1-3 hours, followed by hot extrusion at an extrusion ratio of 10-20:1 and an extrusion speed of 0.05-0.2 mm / s.

6. The preparation method according to any one of claims 1-5, characterized in that, The NiTi alloy powder is spherical Ni with a particle size ranging from 1 to 30 μm. 55 Ti 45 powder.

7. The preparation method according to claim 6, characterized in that, The magnesium alloy powder is a spherical Mg-6Gd-3Y-0.5Zr alloy powder with a particle size range of 20-70μm.

8. A nickel-titanium particle-reinforced magnesium matrix composite material prepared by the preparation method according to any one of claims 1-7.